The mistress memoirs - Hunter, Jillian (Thorndike, Maine : Center Point Large Print, 2014)
Courtesan Georgette Lawson entrusts governess Kate Walcott with the care of her unruly children and the writing of her shocking memoirs, but when Colin Boscastle, Georgette's first lover, comes back to restore his honor and avenge his father's murder, Kate's finds her heart at risk.
Keywords: Governesses -- Fiction; Courtesans -- Fiction; Large type books; Great Britain -- History -- George III, 1760-1820 -- Fiction; Love stories; Historical fiction